1988
DOI: 10.1084/jem.167.2.612
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2 receptor-targeted cytotoxicity. Interleukin 2 receptor-mediated action of a diphtheria toxin-related interleukin 2 fusion protein.

Abstract: Over the past decade there has been considerable interest in the assembly of conjugate toxin molecules whose action is directed toward specific target cells. A wide variety of cell surface-directed ligands (e.g., mAbs, lectins, polypeptide hormones, growth factors) have been coupled through disulfide linkage to nontoxic fragments of plant and/or microbial toxins (reviewed in 1, 2) . In particular, mAbs have been used to direct the cytotoxic action of ricin, both the A chain and intact toxin, and fragments of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(62 citation statements)
references
References 41 publications
0
62
0
Order By: Relevance
“…22,23 The susceptibility of both normal and neoplastic cells to denileukin diftitox-induced cytotoxicity is dependent on the expression of the high-affinity IL-2R, consisting of the p55 (␣), p75 (␤), and p64 (␥) subunits. [24][25][26] The inhibitory concentration of 50% (IC 50 ) of high-affinity IL-2R-expressing cells is 10 Ϫ12 M, whereas cells expressing intermediate-affinity receptors (p75, p64) are intoxicated at an IC 50 of 10 Ϫ10 M. 27 Cells expressing only p55 are relatively resistant (IC 50 of 10 Ϫ8 M). Expression of high-affinity IL-2R is restricted to activated T lymphocytes, activated B lymphocytes, and activated macrophages, whereas intermediate-affinity receptors are found on natural killer cells and resting T cells.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The susceptibility of both normal and neoplastic cells to denileukin diftitox-induced cytotoxicity is dependent on the expression of the high-affinity IL-2R, consisting of the p55 (␣), p75 (␤), and p64 (␥) subunits. [24][25][26] The inhibitory concentration of 50% (IC 50 ) of high-affinity IL-2R-expressing cells is 10 Ϫ12 M, whereas cells expressing intermediate-affinity receptors (p75, p64) are intoxicated at an IC 50 of 10 Ϫ10 M. 27 Cells expressing only p55 are relatively resistant (IC 50 of 10 Ϫ8 M). Expression of high-affinity IL-2R is restricted to activated T lymphocytes, activated B lymphocytes, and activated macrophages, whereas intermediate-affinity receptors are found on natural killer cells and resting T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Denileukin diftitox (Ontak) is a recombinant IL-2/diphtheria toxin conjugate that is designed to direct the cytotoxic action of diphtheria toxin to cells that express the IL-2R (26). Thus far, clinical studies in which Ontak was administered to melanoma patients showed that it may reduce the number of circulating Tregs and cause regression of melanoma metastases (27)(28)(29).…”
mentioning
confidence: 99%
“…It encoded a 68-kDa protein containing the first 486 amino acids of DT and the full-length sequence for IL-2. 18,19 It was extensively studied in the late 1980s and early 1990s and had modest success in phase I and II clinical trials against various lymphoid malignancies (intermediate-and low-grade non-Hodgkin lymphoma, Hodgkin disease, cutaneous T cell leukemia (CTCL)). 20 However, an exceptionally short in vivo half-life (related in large part to its hydrophobicity and tendency to aggregate in solution) prompted efforts to improve on the original design.…”
mentioning
confidence: 99%